Training of cultural agents, rurality and heritage: an experience of community education (Praxis Educativa, 2022)
The objective of the following article is to present the methodological process through which the implementation of a community pedagogical proposal was achieved in a rural context, focused on the training of cultural agents with incidence in the field of heritage and tourism. For the development of this proposal, the academic community of the rural Pan-American School Puente de Boyacá, their families and the inhabitants of the villages of Ventaquemada and Tunja in Boyacá - Colombia participated. The results allowed concluding that heritage pedagogy needs to be approached from community processes that allow critical reflection, dialogic learning and understanding of the socio-cultural environments where they are developed, being this one of the many scenarios that favor the generation of popular cultural agents (PCA).
Keywords: pedagogy; cultural heritage; cultural agent; school-community relationship; dialogue